The crystal structure of (E)-6-bromo-3,5-dimethyl-2-(1-phenylprop-1-en-2-yl)-3Himidazo[4,5b]pyridine, C17H16BrN3 - Bogdanov Ivan P.; Stammler Hans-Georg; Tzvetkov Nikolay T. (Zeitschrift für Kristallographie - New Crystal Structures, 2024)
C17H16BrN3, monoclinic, P21/c (no. 14), a = 6.91863(13) Å, b = 7.17190(11) Å, c = 29.6309(5) Å, β = 93.9228(15)∘, V = 1466.83(4) Å3, Z = 4, Rgt(F) = 0.0201, wRref(F2) = 0.0392, T = 100.0(1) K.